The Effect of Exercises Using Rubber Ropes for Developing Boxing Skill Performance of Torso Rotation and Explosive Power in Youth Boxers - Mohammed, Deham; Jalal, Kmal (Journal of Physical Education, 2020)
The research aimed at shedding the light on skill performance of torso rotation during boxing a problem that faces most coaches during training. The researchers founded that explosive power have a great effect on boxer’s performance thus they designed exercises using rubber ropes to develop skill performance of boxing while torso rotation and explosive power in youth boxers. The researchers used the experimental method on (20) boxers from the national center for gifted in boxing who were divide into two equal groups; experimental and controlling groups. The results showed that rubber ropes have great positive effects on boxers from both the skill aspect and physical aspect.